Methane Adsorption Characteristics of coals from Sambaliung area,Berau, East Kalimantan and Sawahlunto area, West Sumatra, Indonesia - Anggayana, Komang; Kamarullah, Denny Reza; Suryana, Asep; Widayat, Agus Haris (Pusat Survei Geologi, 2017)
Investigation of methane adsorption capacity has been performed in Sambaliung Area, Berau, East Kalimantan (Latih Formation) and Sawahlunto Area, West Sumatra (Sawahlunto Formation). The study involves some analyses: methane sorption, petrography, and proximate. Adsorption isotherm analysis reveals storage capacity of Sambaliung and Sawahlunto coals about 113 to 269 scf/ton (daf) and from 486 to 561 scf/ton (daf), respectively. The adsorption capacity of the coals is thought to be related with formation pressure represented by depth as well as coal rank. The Sambaliung coal rank is low as indicated by the lower vitrinite reflectance (Rr about 0.38%) and higher total moisture (TM about 31%, ar). The Sawahlunto coal rank is higher as indicated by higher Rr (about 0.72%) and lower TM (about 6%, ar).